Novel approach for preparation of poly (ionic liquid) catalyst with macroporous structure for biodiesel production. (15th November 2016) - Wu, Zuowang; Chen, Chong; Guo, Qirui; Li, Bingxue; Que, Yigen; Wang, Lei; Wan, Hui; Guan, Guofeng
Graphical abstract: Multi-layered macroporous poly (ionic liquid) with repeating catalytic units proves to be a novel and efficient heterogeneous acidic catalyst for biodiesel production. Highlights: The catalyst possessed macropore and multi-layered ionic liquid matrix. Fe3 O4 was applied as hard template for the first time. A high biodiesel yield of 92.6% was obtained under mind conditions. The catalyst allowed for a convenient separation with good reusability. Abstract: An efficient poly (ionic liquid) catalyst for biodiesel production was synthesized from Brønsted acidic ionic liquid 1-vinyl-3-(3-sulfopropyl) imidazolium hydrogen sulfate [VSIM][HSO4 ] through free radical polymerization from a novel approach, where Fe3 O4 particles acted as hard template. The template could be easily removed in short time and macrospores formed after the removal of Fe3 O4 . The structure of the polymer was characterized by different techniques and the results demonstrated that the macroporous polymeric network was multi-layered and exhibited repeating units of SO3 H and HSO4 with fine separation efficiency, as a novel heterogeneous acidic catalyst. The catalytic performance of the macroporous polymer was assessed in the esterification reaction of oleic acid for biodiesel production and the Box-Behnken response surface methodology (RSM) was applied for maximizing the biodiesel yield by optimizing process variables at 80 °C. Under the optimum conditions (reaction time was 4.5 h, catalyst amount was 8.5 wt%, and alcohol/acid molar ratio was 12:1), a high biodiesel yield of 92.6% was obtained. The polymeric catalyst also showed favorable reusability after six runs. The combination of macrospores with poly (ionic liquid) would significantly reduce the limitation of mass transfer in biodiesel production compared with other porous solid acidic catalysts.